Panofsky e Florenskij: un incontro mancato. Fenomenologia del simbolico nella rappresentazione prospettica (Lebenswelt. Aesthetics and philosophy of experience., 2023)
This paper focuses on the theme of perspective representation starting from Panofsky and Florenskij’s works. Aim of this study is to approach this topic not only from an historical, scientific or artistic development, but also including these profiles into a wider framework offered by the philosophical concept of perspective as a symbolic form. I will try to argue that Florenskij’s Reverse perspective “reverses” Panofsky’s The perspective as symbolic form, without neglecting assumptions but rather delving in deeper analyses and integrating it with a phenomenological point of view.